Multiwavelength Sun-as-a-star Analysis of the M8.7 Flare on 2022 October 2 Using Hα and EUV Spectra Taken by SMART/SDDI and SDO/EVE - Takato Otsu; Ayumi Asai (The Astrophysical Journal, 2024)
This paper presents a multiwavelength Sun-as-a-star analysis of the M8.7 flare on 2022 October 2, which was associated with a filament eruption and the subsequent coronal mass ejection. The Sun-as-a-star analysis was performed using H α data taken by Solar Dynamics Doppler Imager on board the Solar Magnetic Activity Research Telescope at Hida Observatory, Kyoto University, and full-disk integrated extreme ultraviolet (EUV) spectra taken by the Extreme ultraviolet Variability Experiment (EVE) on board the Solar Dynamics Observatory. The Sun-as-a-star H α spectra showed blueshifted absorption corresponding to the filament eruption. Furthermore, the EVE O v 629.7 Å spectra showed blueshifted brightening, which can also be attributed to the filament eruption. Even when the blueshifted absorption became almost invisible in the Sun-as-a-star H α spectra, the O v blueshifted brightening up to −400 km s ^−1 was still clearly visible. This result indicates that even when the shifted components—which are expected to originate from stellar eruptions—become almost invisible in the spatially integrated stellar H α spectra, the erupting materials may still be present and observable in EUV spectra. Additionally, the Sun-as-a-star H α and O v spectra exhibited redshifted absorption and brightening, respectively, during the decay phase of the flare. These components probably originate from the post-flare loops, providing clues to the multitemperature nature of the post-flare loops in the spatially integrated observation. Our Sun-as-a-star results suggest that the combination of H α and EUV lines allows the investigation of the multitemperature structure and temporal development of stellar active phenomena even in spatially integrated spectra.